The Impact of Operational and Financial Hedging to the Airline Operating Performance - Dewikristi Siallagan , Sitauli; Prijadi, Ruslan (KnE Social Sciences, 2020)
The airline is a low-profit margin and high competition industry. Increasing competition makes airline unable to easily charge their costs to customers and raise their fare, so that airlines have a narrow profit margin. One of the major costs in the airline industry is jet-fuel cost. International Air Transport Association (IATA), predict that total global fuel cost for period 2019 will rise to USD 200 billion from about USD 180 billion in 2018. In average, Jet fuel will contribute 24.2 percent of total 2019 Airline’s operating cost (IATA [1]). Like most of commodities, jet-fuel price is highly volatile which encourages companies to engage in hedging activities. This paper examines the impact of operational and financial hedging to airline operating performance. We perform an empirical study by using the airline data from 2013 to 2017. To test the impact of hedging in airline operating performance, we regress the operating cost to revenue ratio, operational hedging, financial hedging and other control variables. This study found that financial derivative hedge can reduce the dollar needed to generate airline revenue, while operational hedging increase it. Keywords: Fuel Hedging, Operational Hedging, Financial Hedging, Airline Performance